Global Solar Magnetic Field Evolution Over 4 Solar Cycles: Use of the McIntosh Archive - Webb, David F.; Gibson, Sarah E.; Hewins, Ian M.; McFadden, Robert H.; Emery, Barbara A.; Malanushenko, Anna; Kuchar, Thomas A. (Frontiers in Astronomy and Space Sciences, 2018)
The McIntosh Archive consists of a set of hand-drawn solar Carrington maps created by Patrick McIntosh from 1964 to 2009. McIntosh used mainly H, He-I 10830Å and photospheric magnetic measurements from both ground-based and NASA satellite observations. With these he traced polarity inversion lines (PILs), filaments, sunspots and plage and, later, coronal holes over a ~45-year period. This yielded a unique record of synoptic maps of features associated with the large-scale solar magnetic field over four complete solar cycles. We first discuss how these and similar maps have been used in the past to investigate long-term solar variability. Then we describe our work in preserving and digitizing this archive, developing a digital, searchable format, and creating a website and an archival repository at NOAA’s National Centers for Environmental Information (NCEI). Next we show examples of how the data base can be utilized for scientific applications. Finally, we present some preliminary results on the solar-cycle evolution of the solar magnetic field, including the polar field reversal process, the evolution of active longitudes, and the role of differential solar rotation.